Does the Efferent Auditory System Have a Role in Children with Specific Learning Disabilities? - Demirel Aksoy, Emine; Culhaoglu, Belde; Akin Ocal, F. Ceyda; Erbek, Selim Sermed; Erbek, Hatice Seyra (Turkish Archives of Otorhinolaryngology, 2019)
This study aimed to compare the baseline transient otoacoustic emission (t-OAE) amplitudes and medial olivo-cochlear (MOC) efferent activity in children with specific learning disability (SLD) and children with normal development. The study was conducted in two groups. The patient group included 30 children aged 6 to 10 years and diagnosed with SLD, and the control group included 30 children in the same age range without SLD. The patient group included eight males and 22 females, and the control group included 14 females and 16 males. t-OAE and contralateral suppression test were performed in both groups. In the first t-OAE measurements, a statistically significant difference was observed between the patient and the control group at frequencies of 1400, 2000, 2800, and 4000 Hz, but no such difference was observed at 1000 Hz frequency. In the control group, significantly better emission amplitudes were observed. No differences were found at any frequency between the patient and the control groups after suppression. When the subjects in the two groups were compared among themselves, there was a statistically significant difference between the before and after suppression scores in the patient group except at 4000 Hz. Likewise, an important difference was also observed in all frequencies in the control group. This study shows that suppression effects of t-OAE on children diagnosed with SLD and children with no SDL are not significantly different.